pengaruh Pengaruh Model Pembelajaran Think Talk Write Terhadap Pemahaman Konsep IPA Siswa Kelas VII pada Materi Sistem Tata Surya - Tarisa; Skunda Diliarosta; Putri Qalbina; Fatma Wati (Al-Alam: Islamic Science Education Journal, 2026)
Science education in schools today still faces various challenges, one of which is students’ low conceptual understanding, which impacts their learning. Students tend to memorize material without understanding its meaning, the relationships between concepts, and their application in daily life. This situation is exacerbated by a teaching approach that remains teacher-centered. As a result, students’ engagement in thinking, speaking, and writing about what they understand has not yet reached an optimal level. The Think Talk Write (TTW) learning model is an alternative that can be used to address this issue. This study is quantitative and employs a quasi-experimental method with a nonequivalent control group design. Purposive sampling was used to determine the sample. The results of the hypothesis test showed that the significance value was 0.005, which is less than the significance level of 0.05 (p < 0.05). Therefore, H₀ was rejected and H₁ was accepted, indicating that the implementation of the TTW learning model has a significant effect on students’ conceptual understanding. In the class that used the TTW model, students’ conceptual understanding was better than in the class that used the conventional model. Teacher activities and student activities each accounted for 93%. The implementation of the TTW model was rated as “very good.”